A combined approach to characterize ligand‐induced solid–solid phase transitions in biomacromolecular crystals. Issue 3 (9th May 2021) - Ramakrishnan, Saminathan; Stagno, Jason R.; Magidson, Valentin; Heinz, William F.; Wang, Yun-Xing
Abstract : Solid–solid phase transitions in adenine riboswitch crystals are characterized using atomic force microscopy and polarized video microscopy. Abstract : Solid–solid phase transitions (SSPTs) are widespread naturally occurring phenomena. Understanding the molecular mechanisms and kinetics of SSPTs in various crystalline materials, however, has been challenging due to technical limitations. In particular, SSPTs in biomacromolecular crystals, which may involve large‐scale changes and particularly complex sets of interactions, are largely unexplored, yet may have important implications for time‐resolved crystallography and for developing synthetic biomaterials. The adenine riboswitch (riboA) is an RNA control element that uses ligand‐induced conformational changes to regulate gene expression. Crystals of riboA, upon the addition of a ligand, undergo an SSPT from monoclinic to triclinic to orthorhombic. Here, solution atomic force microscopy (AFM) and polarized video microscopy (PVM) are used to characterize the multiple transition states throughout the SSPT in both the forward and the reverse directions. This contribution describes detailed protocols for growing crystals directly on mica or glass surfaces for AFM and PVM characterization, respectively, as well as methods for image processing and phase‐transition kinetics analysis.